STANDARDS OF TEXTUALITY - Asilbek Nazarov (Ustozlar uchun, 2025)
This article explores the concept of textuality through the lens of the seven standards proposed by Beaugrande and Dressler: cohesion, coherence, intentionality, acceptability, informativity, situationality, and intertextuality. It examines how each standard contributes to the formation of a communicative and meaningful text, emphasizing their interdependence in ensuring textual well-formedness and communicative success.